Lateralization in monogamous pairs: wild geese prefer to keep their partner in the left hemifield except when disturbed. Issue 4 (2nd December 2020) - Zaynagutdinova, Elmira; Karenina, Karina; Giljov, Andrey
Abstract: Behavioural lateralization, which reflects the functional specializations of the two brain hemispheres, is assumed to play an important role in cooperative intraspecific interactions. However, there are few studies focused on the lateralization in cooperative behaviours of individuals, especially in a natural setting. In the present study, we investigated lateralized spatial interactions between the partners in life-long monogamous pairs. The male-female pairs of two geese species (barnacle, Branta leucopsis, and white-fronted, Anser albifrons geese), were observed during different stages of the annual cycle in a variety of conditions. In geese flocks, we recorded which visual hemifield (left/right) the following partner used to monitor the leading partner relevant to the type of behaviour and the disturbance factors. In a significant majority of pairs, the following bird viewed the leading partner with the left eye during routine behaviours such as resting and feeding in undisturbed conditions. This behavioural lateralization, implicating the right hemisphere processing, was consistent across the different aggregation sites and years of the study. In contrast, no significant bias was found in a variety of geese behaviours associated with enhanced disturbance (when alert on water, flying or fleeing away when disturbed, feeding during the hunting period, in urban area feeding and during moulting). We hypothesize that the increased demands for right hemisphere processing to deal with stressful and emergency situations may interfere with the manifestation of lateralization in social interactions.